Thiomolybdate [Mo3S13]2− nanocluster: a molecular mimic of MoS2 active sites for highly efficient photocatalytic hydrogen evolution. Issue 6 (20th December 2017) - Lei, Yonggang; Yang, Meiqun; Hou, Jianhua; Wang, Fang; Cui, Entian; Kong, Chao; Min, Shixiong
Abstract : As a MoS2 edge site mimic, the [Mo3 S13 ] 2− nanocluster can efficiently catalyze H2 evolution from a Ru(bpy)3 2+ –H2 A molecular system under visible light. Abstract : Thiomolybdate [Mo3 S13 ] 2− nanoclusters, as a molecular mimic of MoS2 edge sites, showed high efficiency in catalyzing photochemical H2 evolution from a molecular system of Ru(bpy)3 Cl2 –ascorbic acid (H2 A) under visible light irradiation (≥420 nm), providing a turnover number of 1570 and an initial turnover frequency of 335 h −1 for H2 evolution based on the [Mo3 S13 ] 2− catalyst.